2016
DOI: 10.1371/journal.pone.0163424
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cut-Offs of Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) to Identify Dysglycemia and Type 2 Diabetes Mellitus: A 15-Year Prospective Study in Chinese

Abstract: BackgroundThe optimal reference range of homeostasis model assessment of insulin resistance (HOMA-IR) in normal Chinese population has not been clearly defined. Here we address this issue using the Hong Kong Cardiovascular Risk Factor Prevalence Study (CRISPS), a prospective population-based cohort study with long-term follow-up.Material & MethodsIn this study, normal glucose tolerance (NGT), impaired fasting glucose (IFG), impaired glucose tolerance (IGT) and type 2 diabetes mellitus (T2DM) were defined accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 25 publications
3
60
1
2
Order By: Relevance
“…However, diagnostic studies using liver biopsy as the gold standard are not feasible in the community. Secondly, this study was conducted on a Malaysian population and may not be generalizable to other populations, especially since HOMA may vary between different populations . Nevertheless, the results from our study does not differ significantly from that by Boursier et al, suggesting that HOMA estimations do not influence the accuracy of the test.…”
Section: Discussioncontrasting
confidence: 72%
“…However, diagnostic studies using liver biopsy as the gold standard are not feasible in the community. Secondly, this study was conducted on a Malaysian population and may not be generalizable to other populations, especially since HOMA may vary between different populations . Nevertheless, the results from our study does not differ significantly from that by Boursier et al, suggesting that HOMA estimations do not influence the accuracy of the test.…”
Section: Discussioncontrasting
confidence: 72%
“…Pearson correlation analysis showed that the homeostasis model assessment of insulin resistance (HOMA-IR) was positively associated with miR-34a abundance in visceral fat ( Figure 7F; r = 0.3403, P < 0.05), but negatively correlated with KLF4 mRNA levels in the adipose tissue ( Figure 7G; r = -0.3565, P < 0.05). Furthermore, when the overweight/obese subjects were classified into insulin-sensitive (HOMA-IR < 1, n = 8) and insulinresistant groups (HOMA-IR > 1, n = 16) according to the optimal cutoff value determined in our 15-year prospective study (37), the insulin-sensitive subjects exhibited a lower level of miR-34a than those with a higher HOMA-IR value (0.89 ± 0.24 vs. 1.87 ± 0.22, P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…IR is known to increase the risk for the development of dyslipidemia, hypertension, coronary artery disease and, particularly T2D (35,36). Fasting IR indexes, including QUICKI, HOMA-IR, TyG index and the TG/HDL ratio have all been shown to predict incident T2D (37,38,39,40). In our study, individuals in the highest percentile of METS-IR score had a 3.9-fold increase in the risk of incident T2D after follow-up, compared to the lowest METS-IR quartile.…”
Section: Discussionmentioning
confidence: 99%